1984
DOI: 10.1152/ajpendo.1984.247.1.e126
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin profiles during estrous cycle and pregnancy in hamster as measured by homologous RIA

Abstract: The development of a homologous radioimmunoassay (RIA) for the measurement of serum hamster prolactin (PRL) has facilitated our studies on monitoring the secretion patterns of this hormone during different states of reproduction. Four salient findings emerge from the present studies. First, rapid cardiac puncture without anesthesia does not affect serum PRL levels during selected times in the estrous cycle or during pregnancy. Second, serum PRL levels during the estrous cycle describe a daily rhythm of PRL rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…The serum Prl levels measured in this study agree with an other report [24] of the Prl hormone profile during the hamster cycle. In both studies, Prl levels increase on the afternoon of each day with a higher peak during the proestrous surge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The serum Prl levels measured in this study agree with an other report [24] of the Prl hormone profile during the hamster cycle. In both studies, Prl levels increase on the afternoon of each day with a higher peak during the proestrous surge.…”
Section: Discussionsupporting
confidence: 92%
“…The serum LH and Prl levels observed in the present report parallel those reported in previous studies on the hamster es trous cycle [22][23][24], Of interest are the significant daily after noon increases in serum levels of these hormones, highly magnified on the day of proestrus. Although the pattern is re miniscent of that seen in anovulatory hamsters induced by short photoperiod, the magnitude of the daily increase in serum LH levels in anovulatory animals would fall between those observed normally for proestrus and non-proestrus [25].…”
Section: Discussionsupporting
confidence: 90%
“…In fact, a circadian rhythm of PRL secretion has been reported in female golden hamsters in which there is a PRL surge on all days of the estrous cycle (Talamantes et al, 1984) and, to a lesser extent, in djungarian hamsters in which daily PRL surges have been reported throughout the estrous cycle, except on metaestrus (Reburn and Wynne-Edwards, 1996). In rats, it also seems that an endogenous rhythm controls PRL secretion since ovariectomized rats treated with estradiol present daily surges of PRL (Neill, 1972) and some authors describe a small elevation of PRL levels in ovariectomized untreated rats which occurs at the same time of the estradiol-induced surge (Lawson and Gala, 1974;DeMaria et al, 2000), indicating that this apparent rhythm might be modulated by the ovarian steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation of mammary epithelial cells during pregnancy reaches its maximum in the early phase, coinciding with high concentrations of serum hormones such progesterone (44). The high levels of p21 WAF1 and p27 Kip1 expression suggested that activation of cyclin-dependent kinase inhibitors might be responsible for the attenuated cell proliferation in ATF4-transgenic mice during pregnancy.…”
Section: Discussionmentioning
confidence: 99%